Evaluasi Rumah Susun Klender berdasarkan Kriteria Layak Huni - Rizki Dwi Febrina; Djoko Suwandono (Jurusan Perencanaan Wilayah dan Kota, 2022)
The Klender Flats was the first simple flats that were successfully developed by Perum Perumnas in 1985. The Klender Flats has been around for 34 years. When the flats were established, the Klender Flats were expected to solve the problem of slum settlements and squatter settlements by providing a habitable residential environment. Now, the physical condition of Klender Flats is apprehensive and its environmental conditions are no longer maintained. This study aims to evaluate the Klender flats based on adequate housing criteria. The research methode used in this study is descriptive analysis. Then the results of the descriptive analysis are compared with conditions in the field. So, the output produced in this study found that the condition of the Klender flats is declared no longer fulfilling the criteria for adequate housing.